2017
DOI: 10.1007/s00405-017-4840-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between continuous positive airway pressure and serum aminotransferases in patients with obstructive sleep apnea

Abstract: OSA severity was independently associated with liver steatosis and elevation of serum aminotransferases. 3 months of CPAP therapy were associated with a statistically significant improvement on liver injury in OSA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In humans, many associative studies have examined the effect of OSA on hepatic steatosis, with results seemingly supportive of the role of OSA in modulating this early NAFLD phenotype. In fact, several markers of OSA severity have been linked to liver fat content, including AHI (80)(81)(82), time with oxyhemoglobin saturation less than 90% (83), oxyhemoglobin desaturation index (84), and mean (81) and nadir (85) nocturnal oxyhemoglobin saturation. Although some earlier studies were not adjusted for common covariates such as obesity (80), careful multivariate analysis has been performed in larger recent studies.…”
Section: Osa Hypoxia and Hepatic Steatosismentioning
confidence: 99%
“…In humans, many associative studies have examined the effect of OSA on hepatic steatosis, with results seemingly supportive of the role of OSA in modulating this early NAFLD phenotype. In fact, several markers of OSA severity have been linked to liver fat content, including AHI (80)(81)(82), time with oxyhemoglobin saturation less than 90% (83), oxyhemoglobin desaturation index (84), and mean (81) and nadir (85) nocturnal oxyhemoglobin saturation. Although some earlier studies were not adjusted for common covariates such as obesity (80), careful multivariate analysis has been performed in larger recent studies.…”
Section: Osa Hypoxia and Hepatic Steatosismentioning
confidence: 99%
“…However, the available studies have yielded mixed results and are listed in Table 2 and Table 3. 80,[87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102] In these studies, the impact of CPAP therapy on NAFLD was assessed by means of improvements in liver enzymes, hepatic adiposity, or fibrosis. Importantly, the observational studies that demonstrated the benefits of CPAP (see Table 2) were of longer duration than the randomized controlled trials that did not show CPAP to be beneficial (see Table 3).…”
Section: Obstructive Sleep Apnea and Liver Fibrosismentioning
confidence: 99%
“…Similarly, patients with NAFLD have a higher apnoea-hypopnoea index and lower mean nocturnal oxygen saturation than controls (108,109), and these are independent risk factors for progression to hepatic fibrosis (110,111). In addition, increasing severity of OSA appears to be in a dose-relationship with the prevalence of NAFLD (112) and severity of liver dysfunction, both in terms of transaminases (113,114) and liver morphology (115)(116)(117).…”
Section: Lox-1 Overexpressionmentioning
confidence: 99%